Evaluation of the Professional Curriculum of Fine Arts Institutes from the Point of View of Faculty and Students (Journal of the College of Basic Education, 2022)
The aim of this research is to evaluate the professional curriculum of the Institutes of Fine Arts using the opinions of teachers and students. The research presents three levels, the first is theoretical, second is procedural, and third is analytical. The descriptive survey method is used with two random samples from the Institutes of Fine Arts in Baghdad. The first sample included (120) male and female students from the fifth grade, while the second sample included (30) female teachers from all departments of the two institutes. A questionnaire was used as a means of data collection with thirty paragraphs. Students assured that they benefited from educational skill aspects, such as designing instructional plans, dealing with students, and how to benefit from interaction with the school administration and teachers. But they need training in evaluating and caring for the gifted. The faculty indicated the need for the professional curriculum to develop and enrich in dealing with pupils with special needs and develop talents, and the need to work exhibitions and to decorate gardens, as well as cooperation with departments and teachers in a way that makes the art education more acceptable. The research presented important recommendations and suggestions.